Features of existing functional disturbances in patients with chronic obstructive pulmonary disease stage II in the process of integrated therapy with the use of tiotropium bromide - Kulynych-Miskiv, Mariana; Ostrovskyy, Mykola; Savelikhina, Iryna; Ostrovska, Kseniya; Varunkiv, Oleksander (ScienceRise: Medical Science, 2019)
The peculiarities of the disturbances of external respiratory function (ERF) in patients with the second stage of COPD, who received tiotropium bromide are presented. The aim of the study. To evaluate the effect of the baseline therapy of COPD II degree of bronchial obstruction with the use of tiotropium bromide preparation on the parameters of external respiration. Materials and methods. We examined 151 patients with the second stage of COPD. Verification of the diagnosis and its formulation were performed on the basis of the order of the Ministry of Health of Ukraine No. 555 dated June 27, 2013 "On Approval and Implementation of Medical-Technological Documents on Standardization of Medical Assistance in Chronic Obstructive Pulmonary Disease". The examination was perfomed prior to and on the 30th, 90th and 180th days of standard treatment combined with tiotropium bromide. Research results. The analysis of aggregate results showed that the highest efficacy was observed in patients who took tiotropium bromide during 180 days, for in this very period external respiratory function parameters maximally increase. Consequently, such a pronounced effect of the used drug tiotropium bromide as a composite basic treatment for stabilizing the function of external respiration in chronic obstructive pulmonary disease II degree, in our opinion, is due to the mechanism of action characteristic of the drug chosen by us, namely, the clear prolonged bronchodilator effect. Conclusions. Our treatment regimens have a pronounced influence on a number of important pathogenetic links in the course and progression of chronic obstructive pulmonary disease, especially in the initial stages, which clearly confirms the need for early detection of this pathology and early onset of its therapy. They are characterized by simplicity and accessibility, high clinical efficacy, the absence of adverse reactions and complications.